Itching-like behavior: A common effect of the kappa opioid receptor antagonist 5'-guanidinonaltrindole and the biased kappa opioid receptor agonist 6'-guanidinonaltrindole in mice - Alan Cowan; Lee-Yu; Saadet Inan (Elsevier, 2021)
Activation of the KOR produces antipruritic effects. In this study, we investigated three KOR ligands for their abilities to cause scratching behaviors in mice, an animal model of itch, and the involvement of the KOR in these behaviors. Two regioisomers are especially interesting: 6'-guanidinonaltrindole (6'-GNTI, a reportedly KOR G protein-biased agonist) and 5'-guanidinonaltrindole (5'-GNTI, a KOR antagonist). 5'-GNTI is known to precipitate frenzied, excessive scratching in mice. Here we report for the first time that 6'-GNTI causes comparable itching-like behavior in this species, which was not affected by KOR deletion in mice, indicating that it is not mediated by the KOR. We further studied the KOR antagonist LY2456302 (Aticaprant), which is in clinical trials for treatment of substance abuse, for scratching effect in both wild type and KOR knock out mice. Similar numbers of scratches were observed in wild type and KOR knock out mice. We call attention to pruritus as a possible negative side effect of KOR antagonists and 6'-GNTI in humans.